Interregional comparisons of agricultural production efficiency in the Ethiopian highlands - Ehui, Simeon K.; Paulos, Z.; Solomon, S.; Benin, Samuel; Gebremedhin, Berhanu; Jabbar, M.A.; Pender, J.L. (International Food Policy Research Institute, 2002)
The diversity of agro-ecological zones in Ethiopia and variations in region-specific policies leads to an assumption that agriculture is fairly diverse regionally. The regional differentiation due to agro-ecology, policies and programmes leads one to expect variations in factor returns, allocations and productivity by region. This paper presents interregional comparisons of agricultural production efficiency in the Ethiopian highlands based on data from extensive community, household and plot surveys conducted for the production year 1999-2000 in three regions of Ethiopia, namely, Amhara, Oromiya and Tigray. The paper ends with comment by Stein Holden